Sepsis - Estudo Observacional Retrospectivo de Sépsis e Choque Séptico na Enfermaria de Medicina Interna - Sónia Santos; Ana Ponciano; Joana Raquel Monteiro; Fernanda Pinhal; José Leite; Célio Fernandes (Sociedade Galega de Medicina Interna, 2020)
Introduction: Sepsis and septic shock are very relevant in clinical practice. Most studies focus on the treatment in Intensive Care Units. Outside these units, the reality is largely unknown. The aim of this study is to epidemiologically characterize sepsis and septic shock patients admitted at internal medicine wards. Material and Methods: Retrospective observational study, involving patients admitted to internal medicine wards with the diagnosis of sepsis/septic shock during a year Results: A total of 308 patients were included in the study. 53% were female, with higher levels of comorbidities. Almost 40% were in septic shock, at admittance. Mortality rate was 29,87%. Overall, microbiologic documentation was possible in 92.2% of the cases, with higher prevalence of infection in the urinary (52.6%) and respiratory (34.8%) systems. Initial antibiotic therapy was appropriate in 50% of cases. Previous antibiotic therapy (OR 3.84; IC95% 2.4-6.2; p<0.0001) and bedridden status (OR 3.15; IC95% 1.7-5.8; p<0.0002) were independent risk factors to antimicrobial resistance. Discussion: Sepsis outside intensive care units is an escalating reality with high rates of morbidity and mortality. Timely diagnosis and collecting cultures to appropriate treat are primordial to best results. Conclusion: This study provides data regarding sepsis/septic shock treated outside intensive care units, that allow a better knowledge of this reality so that it is possible to plan strategies to best attend these patients. Prospective analysis to consolidate criteria for diagnosis, follow-up and prognosis of these patients, as well as review of protocols of action are needed.